Exploring the perceptions of psychiatric patients regarding marijuana use - Leepile A. Sehularo; Emmerentia du Plessis; Belinda Scrooby (AOSIS, 2012)
There is limited understanding on marijuana use by psychiatric patients, specifically with regard as to why they continue to smoke marijuana despite the negative consequences, such as readmittance to psychiatric hospitals following marijuana-induced psychosis. It is, therefore, important to understand why psychiatric patients continue to use marijuana, despite experiencing its negative effects. The purpose of this study was to explore and describe the perceptions of psychiatric patients with regard to marijuana use in Potchefstroom, North West Province, as well as to formulate recommendations for nursing education, nursing research and nursing practice, with the aim of reducing the readmission of psychiatric patients following marijuana-induced psychosis. A qualitative, exploratory, descriptive and contextual research design was followed in order to give 'voice' to the perceptions of psychiatric patients about marijuana use. Purposive sampling was utilised to identify participants who complied with selection criteria. The sample size was determined by data saturation, which was reached after 10 individual interviews with psychiatric patients. Unstructured individual interviews were utilised to gather data after written approval from the Ethics committee of the North-West University (Potchefstroom Campus), North West Provincial Department of Health, the clinical manager of the psychiatric hospital where data were collected, as well as from the psychiatric patients. The co-coder and the researcher analysed the data independently. The findings of this study include perceptions of psychiatric patients on the use of marijuana, the negative effects of marijuana use, marijuana use and mental illness, and quitting marijuana. Recommendations were formulated for nursing education, nursing research as well as for nursing practice. Opsomming Insig in die gebruik van marijuana deur psigiatriese pasiënte is beperk, spesifiek met betrekking tot hulle redes vir voortgesette marijuana verbruik ten spyte van die negatiewe gevolge daarvan, byvoorbeeld hertoelating tot psigiatriese hospitale na marijuanageïnduseerde psigotiese episodes. Dit is dus belangrik om te verstaan waarom psigiatriese pasiënte voortgaan om marijuana te gebruik ten spyte van die negatiewe uitwerking daarvan. Hierdie navorsing was ten doel om die persepsies van psigiatriese pasiënte in verband met die gebruik van marijuana in Potchefstroom in die Noordwesprovinsie te verken en te beskryf. So kan aanbevelings gemaak word vir verpleegonderrig, verpleegnavorsing en verpleegpraktyk om meer toepaslike versorging en behandeling te verseker en uiteindelik die heropname van psigiatriese pasiënte as gevolg van marijuana-geïnduseerde psigose te verminder. 'n Kwalitatiewe, verkennende, beskrywende en kontekstuele navorsingsontwerp is gevolg om 'n 'stem' te gee aan die persepsies van psigiatriese pasiënte aangaande die gebruik van marijuana. Doelgerigte steekproefneming is gebruik om deelnemers te identifiseer wat sou voldoen aan seleksiekriteria. Die steekproefgrootte is bepaal deur dataversadiging, wat bereik is na 10 individuele onderhoude met psigiatriese pasiënte. Ongestruktureerde individuele onderhoude is gebruik om data te versamel ná geskrewe toestemming van die Etiekkomitee van die Noordwes-Universiteit (Potchefstroom Kampus), van die Noordwes Provinsiale Departement van Gesondheid, die Kliniese bestuurder van die psigiatriese hospitaal waar die data versamel is, sowel as van die psigiatriese pasiënte. Die medekodeerder en die navorser het die data onafhanklik van mekaar geanaliseer. Die bevindings van hierdie studie het die persepsies wat psigiatriese pasiënte het oor die gebruik van marijuana, die negatiewe effekte van die gebruik van marijuana, die gebruik van marijuana en psigiatriese toestande, en die staking van die gebruik van marijuana, uitgelig. Aanbevelings is geformuleer vir verpleegonderrig en verpleegnavorsing, sowel as vir die praktyk van verpleegkunde.